Evaluation of urohyal bone for age determination in Monopterus albus (Zuiew, 1793) - Sow, A. Y.; Zulkifli, S. Z.; Ismail, A (Indian Journal of Fisheries, 2015)
Present study aimed to determine the age of Asian paddy eel Monopterus albus using the urohyal bone. Majority of fish ages ranged between three and four years and were immature. Strong relationship between total length and body weight (R2=0.937) was observed in M. albus. Further studies would justify the suitability of urohyal bone for determining the age of M. albus.